KEANEKARAGAMAN DAN KELIMPAHAN JENIS LIANA (TUMBUHAN MEMANJAT) PADA HUTAN ALAM DI HUTAN PENDIDIKAN UNIVERSITAS HASANUDDIN - . Asrianny; . Marian; Ngakan Putu Oka (Forestry Faculty of Universitas Hasanuddin, 2009)
Liana is group of climbing species which is typical and characterize the tropical rain forest. This species have important value both ecologically and economically. However, data on this group on species in South Sulawesi, in particular in the Hasanuddin University Experimental Forest is not yet available.This study aimed to determine the diversity and abudance liana species present in the natural forest area of Hasanuddin University Experimental Forest. 15 plots was set in the order to observe the diversity and abudance of liana species. The data were analysed and presented interm of important value index, diversity index, abudance index, and evenness index. The results showed that there were various species of liana in which there were found 81 species, consist of 764 individuals. The most common species was Smilax sp, wich mostly claimb on Toona sureni, Buchanania arboreschense and Flacortia rucam as a host. Key words: diversity, abudance, liana, natural forest, Hasanuddin University Experimental Forest